Formal modelling of the electricity markets: the example of the load reduction of electricity mechanism "NEBEF". Issue 1 (November 2021) - Selot, Florian; Robisson, Bruno; Vaglio-Gaudard, Claire; Gil-Quijano, Javier
Abstract: The liberalisation of the electricity market initiated at the beginning of the 21 st century has opened it to new parties. To ensure the growth of participants' number will support the system's balance, the EU regulation 2019/943 confirms that "all market participants should be financially responsible of the imbalances they cause". In their respective area, the transmission system operators develops the regulation in compliance with this condition. However, as the regulation takes into account the new realities of the market such as renewables, the interactions between the participants become more complex. One of the risks is that the imbalance of an actor may not be due to its own actions, not complying with the EU regulation then. To analyse this kind of implicit condition, we propose a formal approach to model the exchanges of energy. Using the French regulation as a base, we model the participants and their interactions in the form of symbolic equations using the energy-related terms as variables. In this paper, to illustrate the model we will use to analyse the entire electricity market, we apply it to the NEBEF mechanism only. This mechanism is dedicated to the selling of demand response in France and introduces a third party between the final producer and the final consumer: the demand response operator. We model the mechanism and analyse how the mechanism complies with the balancing responsibility. Our results demonstrate that the mechanism complies with the regulation but there are some limits due to the calculation method of the reference consumption.